ACCOUNTANTS MORAL JUDGEMENT IN RELIGIOUS AND NON-RELIGIOUS SCHOOL BACKGROUND’S PERSPECTIVE - Hariany Idris; Warka Syachbrani (Hasanuddin Economics and Business Review, 2018)
This study aims to review the conduct of investigation regarding moral judgements between accountants with religious and non-religious school background using moral indicators (moral judgment). Multiple linear regression analysis used in this study. To review the partially relationships between variables, the study operated using T-test, whereas for review simultaneous relationships between variables the study used F-test. This study using 86 respondents as a data source for review processed. The findings of the research is the Religious Background (X1) significantly affected the Accounting students morality judgement (Y), while the difference of Gender (X2) showed the opposite results.